Simulation and Implementation Model of Productivity Measurement Internet Bandwidth Usage - Tjahjanto Tjahjanto; Benhard Sitohang; Sudarso Kaderi Wiryono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
The Internet is used by a very large number of users, from the ordinary  user community, through special users, like people with high intellectual level. The growth in the number of users is increasing very fast. Internet has also been used by multi-sector businesses with multi profession. It makes information the internet usage something very strategic, one of which information productivity internet bandwidth usage. This paper describes a model implementation and simulation of productivity measurement internet bandwidth usage, which describes all possible measurement values obtained, and is a continuation of previous research, which is the basic concept of productivity in the use of internet bandwidth and how to measure it, so that the measuring results can be used as a guide in determine the direction of policy and the provision of productive Internet bandwidth usage.